An Analysis of Commisive Act in the Hunger Games - Moh. Rifki Rasyid; Dwi Taurina Mila Wardhani (Pioneer: Journal of Language and Literature, 2018)
This research was about commissive acts uttered by characters and the aims behind the use of commissive acts in The Hunger Games : Mockingjay Part 2 movie. In conversation, commissive acts are threatening, promissing, vowing, refusing, etc. The research data was in the form of utterances that contained commissive acts uttered by the characters in the movie. To analyze the data, the researcher used Spradley’s theory (1998) which covered : data analysis; domain analysis, taxonomic analysis, componential analysis, and cultural value. This research was conducted by accomodating two theories: Levinson (1983) in analyzing commissive acts and Searle & Vanderveken (1985) in analyzing the aims of commissive acts. The result of the research showed that the were twenty five data that indicated as the relevant data. From the data, the researcher found five aims behind the use of commissive acts in the movie; they were planning, refusing, offering, promising, and threatening. The most dominant aim behind the use of commissive acts were planning (ten data) and promissing (seven data) while the least dominant were refusing (four data), offering ( two data), and threatening (two data).